The Effect of Maternal Creatine Supplementation in Fetal Neuromuscular Development: A Systematic Review - DAA Adlina Febry Maharani Putri; Reza Fitranto Tri Wibowo; Intan Wahyu Lasiaprillianty (Indonesian Journal of Global Health Research, 2026)
Creatine supplementation is a promising neuroprotective strategy during the perinatal period due to its role in energy metabolism and cellular defense. Preclinical studies have explored its potential to mitigate brain injuries caused by hypoxia, anoxia, and metabolic disturbances. However, variability in study designs and administration protocols necessitates a systematic review of existing evidence. To evaluate the effects of maternal creatine supplementation on neuromuscular development in preclinical studies. A PRISMA-guided review searched Scopus, PubMed, ProQuest, and Cochrane databases (from 2000 up to November 25, 2024) for studies on creatine's effects on brain biomarkers, histopathology, and pathophysiology. Studies using creatine or its derivatives as treatment and reporting experimental outcomes with control comparisons were included. An initial database search identified 346 records. Data were synthesized narratively due to models, outcomes, and dosage heterogeneity. Sixteen studies (2000–2023) involving rodents, sheep, pigs, and cultured fetal tissue were identified. Administration methods included oral, intravenous, intraperitoneal, and ex vivo approaches, with treatment primarily during mid-pregnancy to delivery. Fifteen studies reported significant neuroprotective effects, including biomarker improvements (13 studies) and histopathological changes (3 studies), with no adverse effects noted. Creatine shows potential benefits for fetal neurologic and muscular development, but further research is needed to ensure safe translational application.